Hubungan Antara Penguasaan Pengetahuan Lingkungan Hidup Terhadap Etika Lingkungan Siswa SMA - Ade Safitri; Arwin Surbakti; Dewi Lengkana (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2019)
This study aims were (1) describe the closeness correlation between mastery of environmental knowlagde with students environmental ethic of SMAN 1 Natar; (2) describe  the direction correlation between mastery of environmental knowlegde with students environmental ethics of SMAN 1 Natar; and (3) to know the contribution of the mastery of environmental knowlegde to students environmental ethics of SMAN 1 Natar. The design was the one shot case study design.The samples was 108 at tenth grade students of the Mathematics Department of Nature Sciences. The sample were taken by purposivesampling technique. The data of knowledge of environmental knowledge were obtained through reasoned T-F test questions and data of environmental ethics were obtained through questionnaires. The data was analyze by Pearson Product Moment. The result of correlation test and linear regression test showed that there was moderate relationship between mastery of environmental knowlagde with of environmental ethics of students in SMAN 1 Natar  with correlation coefficient of 0.387 which contributed 15% with a positive direction.Penelitian ini bertujuan untuk: (1) Mendeskripsikan keeratan hubungan antara penguasaan pengetahuan lingkungan hidup terhadap etika lingkungan siswa SMAN 1 Natar; (2) Mendeskripsikan arah hubungan antara PPLH terhadap EL siswa SMAN 1 Natar; dan (3) Mengetahui besar kontribusi penguasaan PPLH terhadap EL  siswa SMAN 1 Natar. Desain penelitian adalah The One Shot Case Study. Sampel penelitian  yaitu 108 siswa kelas X Jurusan MIA. Sampel menggunakan teknik purposive sampling.  Data hasil penelitian berupa data PPLH diperoleh melalui tes soal B-S beralasan dan data EL diperoleh melalui angket. Data hasil penelitian dianalisis menggunakan uji Pearson Product Moment. Hasil uji korelasi dan regresi linier menunjukkan adanya hubungan yang moderat antara PPLH terhadap EL siswa SMAN 1 Natar dengan nilai koefisien korelasi sebesar 0.387 memberikan kontribusi 15% dengan arah hubungan positif.Kata kunci: pengetahuan lingkungan hidup, etika lingkungan, lingkungan